Effects of Carbonization Temperature from Activated Carbon of Water Hyacinth on the Flux and Its Ability on Iron Removal - Maulina, Wenny; Priyanto, Frendi Wahyudi; Arkundato, Artoto (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
The synthesis of activated carbon derived from water hyacinth has been successfully carried out as an iron adsorbent in a laboratory-scale water filter design system. In this article, activated carbon derived from water hyacinth is made through a carbonization process at 400°C and 500°C with NaOH as an activating agent. This activated carbon derived from water hyacinth acts as a filter media for purifying well water by assessing the flux, pH and iron removal efficiency before and after filtration. The results showed that the use of activated carbon derived from water hyacinth with a carbonization temperature of 500°C resulted in a water flux value greater than the carbonization temperature of 400°C. The pH value showed no difference between the use of activated carbon derived from water hyacinth (at a carbonization temperature 400°C and 500°C) before and after the filtration process, which was 7.5. Meanwhile, the effectiveness of activated carbon derived from water hyacinth at a carbonization temperature of 500°C as a filtration medium is more optimal in reducing iron levels compared to the use of activated carbon at a carbonization temperature of 400°C with percentage efficiency up to 98.09%.